First Prospective Multicenter Italian Study on the Impact of the 21‐Gene Recurrence Score in Adjuvant Clinical Decisions for Patients with ER Positive/HER2 Negative Breast Cancer. (28th November 2017) - Dieci, Maria Vittoria; Guarneri, Valentina; Giarratano, Tommaso; Mion, Marta; Tortora, Giampaolo; De Rossi, Costanza; Gori, Stefania; Oliani, Cristina; Merlini, Laura; Pasini, Felice; Bonciarelli, Giorgio; Griguolo, Gaia; et al.
Abstract : Background: The Breast DX Italy prospective study evaluated the impact of the 21‐gene recurrence score (RS) result on adjuvant treatment decisions for patients with early breast cancer. Materials and Methods: Nine centers (two Hub and seven Spoke centers of the Veneto Oncology Network) participated. Consecutive patients with estrogen receptor positive, human epidermal growth receptor negative, T1–T3, N0–N1 early breast cancer were prospectively registered; only those meeting protocol‐defined clinicopathological "intermediate risk" criteria were eligible for the RS test. Pre‐RS and post‐RS physicians' treatment recommendations and treatment actually received were collected. Results: A total of n = 124 N0 and n = 126 N1 patients underwent the RS assay. The majority had Grade 2 tumors (71%); median age was 55 years, median tumor size was 16 mm, and median Ki67 expression was 20%. Patients enrolled at Hub centers presented higher‐risk features. The distribution of RS results was <18 (60.8%), 18–30 (32.4%), and >30 (6.8%). The indication before RS was hormonal therapy (HT) alone in 52% of cases. An indication before RS of chemotherapy (CT)+HT was more frequent for patients with N1 versus N0 tumors (57% vs. 39%, p = .0035) and for patients enrolled at Hub versus Spoke centers (54% vs. 36%, p = .007). The overall rate of change in treatment decision was 16% ( n = 40), mostly from CT+HT to HT ( n = 30). According to nodal status, rate of change in treatment decision was 12% for the N0 cohort and 20% for the N1 cohort. The proportion of patients recommended to CT+HT was significantly reduced from before to after RS (48% to 40%, p < .0016), especially in the N1 cohort (57% to 45%, p = .0027) and at Hub centers (54% to 44%, p = .001). Conclusion: Despite frequent indication of HT before RS, the use of the RS assay further contributed to sparing CT, especially for patients with N1 tumors and at Hub centers. Implications for Practice: This study shows that, although a high proportion of patients were recommended to receive endocrine treatment alone before knowing the recurrence score (RS) assay, the RS test further contributed in sparing chemotherapy for some of these patients, especially in case of the N1 stage or for patients enrolled at referral centers. These data highlight the need for further work in collaboration with health authorities and companies in order to define strategies for the implementation of the use of RS testing in clinical practice in the Italian setting. Abstract : The Breast DX Italy prospective study was designed to evaluate the impact of the 21‐gene Oncotype DX recurrence score assay on adjuvant treatment decisions for patients with early breast cancer. Results of the study are reported here.